2003
DOI: 10.1007/978-3-540-45243-0_21
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally Invariant Wavelet Shrinkage

Abstract: Abstract. Most two-dimensional methods for wavelet shrinkage are efficient for edge-preserving image denoising, but they suffer from poor rotation invariance. We address this problem by designing novel shrinkage rules that are derived from rotationally invariant nonlinear diffusion filters. The resulting Haar wavelet shrinkage methods are computationally inexpensive and they offer substantially improved rotation invariance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…SΛ denotes the coupled shrinkage functioñ (Chambolle 2005;Mrázek and Weickert 2003;Welk et al 2008). Similarly, we obtain…”
Section: Application To Image Denoisingmentioning
confidence: 99%
See 1 more Smart Citation
“…SΛ denotes the coupled shrinkage functioñ (Chambolle 2005;Mrázek and Weickert 2003;Welk et al 2008). Similarly, we obtain…”
Section: Application To Image Denoisingmentioning
confidence: 99%
“…The corresponding circulant matrices are denoted by H 0 ∈ R n,n and H 1 ∈ R n,n . Then, the following matrix fulfills W * W = I N but WW * = I 4N : Mrázek and Weickert (2003) and Welk et al (2008) showed that…”
Section: Total Variation Regularizationmentioning
confidence: 99%
“…Mrazek and Weickert [52] presented a translation and rotation invariant method that combines wavelet transforms with nonlinear diffusion filters. The iterated filter is not completely rotation invariant, but the asymmetry decreases with a higher number of iterations.…”
Section: Invariance; Review Of Previous Workmentioning
confidence: 99%
“…In [13], the authors proposed to choose a diffusion inspired shrinkage function that simultaneously depends on c 1,2 , c 2,1 and c 2,2 . In contrast to the classical wavelet shrinkage, this results in an improved rotation invariance of the resulting image.…”
Section: Haar Wavelet Shrinkagementioning
confidence: 99%
“…It does not require regularised diffusivities of type (5). Interestingly, it can also be related to a recently introduced family of shift invariant wavelet shrinkage methods with coupled shrinkage functions [13].…”
mentioning
confidence: 99%